Critical analysis of data of Afghan transit through Pakistan since 2010: Trends, Issues, Challenges and Way Forward - Shah, Zubair (Journal of Pakistan Administration, 2023)
Pakistan extends the transit trade facility to Afghanistan under bilateral and international frameworks. British India extended this facility and so did Pakistan. But transit and trade has never been consistent. This research focuses on the trends of transit data, issues and challenges and the way forward for Afghan Transit and beyond. The study uses analytical and descriptive approaches. Qualitative data has been collected through interviews while quantitative data has been obtained from official records, research articles, websites, social and other media searches. The research concluded that the old transit trade agreement was not meeting the challenges of structured transit as per international best practices and a new treaty APTTA was signed in 2010 with the active collaboration of the international community and since then transit has passed through different phases. The paper explores the current legal and institutional transit trade regime and trends of transit trade since 2010 with specific focus on the last five years. It has passed through diverse phases due to mutual mistrust, weak institutional arrangement, smuggling, lack of proper infrastructure, transit trade security and data issues, The Paper also highlights the impact of international politics and the development of port infrastructure in Iran and Afghanistan by India. The paper advocates for a policy shift from geostrategic to geo-economic cooperation, focusing on mutual and transit trade. It emphasizes the need for regional connectivity, effective border controls, and breaking the transit smuggling nexus. Strengthening institutional arrangements, promoting transparency, and simplifying procedures are recommended to enhance transit trade and foster economic ties between the two countries.